The First, Comprehensive, Open-Source Culinary Medicine Curriculum for Health Professional Training Programs: A Global Reach. Issue 4 (July 2020) - Hauser, Michelle E.; Nordgren, Julia R.; Adam, Maya; Gardner, Christopher D.; Rydel, Tracy; Bever, Alaina M.; Steinberg, Emma
Providing a strong foundation in culinary medicine (CM)—including what constitutes a healthy diet and how to find, obtain, and prepare healthy and delicious food—is a cornerstone of educating health professionals to support patients in achieving better health outcomes. The Culinary Medicine Curriculum (CMC), published in collaboration with the American College of Lifestyle Medicine, is the first, comprehensive, open-source guide created to support the implementation of CM at health professional training programs (HPTPs) worldwide. The CMC is modeled after the successful CM elective course for Stanford University School of Medicine students. Key goals of the CMC include presenting healthy food as unapologetically delicious, quick, and inexpensive; translating lessons learned to healthy eating on-the-go; practicing motivational interviewing on healthy dietary behavior changes; and demonstrating how to launch a CM course. The CMC highlights a predominantly whole food, plant-based diet as seen through the lenses of different world flavors and culinary traditions. It was developed, published, and distributed with the aim of expanding CM by reducing barriers to creating CM courses within most types of HPTPs and practice settings. During the first 2 months the CMC was available, it was downloaded 2379 times in 83 countries by a wide variety of health care professionals interested in teaching CM. The global interest in this first, freely available, evidence-based CMC underscores the demand for CM resources. Such resources could prove foundational in expediting development of CM courses and expanding the reach of CM and counseling on dietary behavior changes into patient care.